Nonlinear association between blood urea nitrogen to creatinine ratio and obstructive sleep apnea: a cross-sectional study from NHANES - Lei Yang; Lanying Li; TingTing Zeng; Yang Li; Yating Li; DePeng Jiang; Hongmei Yue (BMC Pulmonary Medicine)
Abstract Background Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder that is closely associated with metabolic conditions. The Blood Urea Nitrogen to Creatinine Ratio(BUCR) is commonly utilized as a tool for evaluating renal function, particularly in cases where there are concerns about pre-renal or renal causes of azotemia. However, the connection between OSA and BUCR is not yet fully understood. Methods This study examined the link between BUCR and OSA in adults over 20 using National Health and Nutrition Examination Surveys(NHANES) data from 2005–2008. Logistic regression models adjusted for multiple variables were used to analyze the relationship. The non-direct correspondence relationship were explored with a smooth curve and a two-part linear regression model, which revealed a threshold effect. Subgroup analyses were conducted to assess variations among different populations. Results The survey, encompassing a total of 8826 participants, revealed that the median age of all respondents was 48 years, with a notable OSA prevalence of 51.3%. Upon adjusting for pertinent covariates using Model III(age, sex, marital status, education level, BMI, smoking status, drinking, hypertension, and diabetes), our findings indicated a significant association between OSA and BUCR, as evidenced by an odds ratio (OR) of 1.01 (95% CI: 1.00–1.02, P = 0.005). Furthermore, the risk association was found to be non-linear, featuring an inflection point for BUNR at 10.86. This non-linear relationship adds complexity to our understanding of the interplay between OSA and BUCR. In addition, a subgroup analysis underscored the influence of diabetes on the association between BUCR and OSA. Conclusion This study reveals a significant correlation between elevated BUCR levels and the incidence of OSA, particularly in the presence of diabetes. This discovery underscores the necessity for additional research to investigate the underlying mechanisms and ramifications of this connection within the diabetic context.